Discovering meaning behind consumer involvement in Counterfeit consumption behaviour - Rosely, Nurhidayah; Raja Yusof, Raja Nerina; Hashim, Haslinda; Adzharuddin, Nor Azura (Human Resource Management Academic Research Society, 2019)
The rising demand on counterfeit goods has led to a new phenomenon in consumer behavior. Counterfeit goods have long been labelled as inferior in quality, and often targeted at consumers with low purchasing power. However, current trends show that there is a rise in the number of consumers who willingly purchase counterfeit goods despite being able to afford the original merchandise. This paper seeks to explain the phenomenon of non-deceptive counterfeit goods demand among Malaysian consumers by analyzing consumer meaning from real life experiences. The concept of consumer rationalization on this unethical practice leads to the construction of meaning behind consumer involvement in counterfeit consumption behavior. This research reveals three themes of meaning behind consumer involvement namely: “It’s just a fading material object”, “It’s just the right time” and “I need to protect it”. This research is also one of the few studies that identify the meaning behind consumer involvement in counterfeit consumption from the perspective of the consumers’ real-life experience. This paper contributes to the scholarly and managerial fields specifically in the Malaysian context by providing more insights into this phenomenon.